Alpha/Beta-Hydrolase Domain-Containing 6: Signaling and Function in the Central Nervous System - Haofuzi Zhang; Xin Li; Dan Liao; Peng Luo; Xiaofan Jiang (Frontiers Media S.A., 2021)
Endocannabinoid (eCB) signaling plays an important role in the central nervous system (CNS). α/β-Hydrolase domain-containing 6 (ABHD6) is a transmembrane serine hydrolase that hydrolyzes monoacylglycerol (MAG) lipids such as endocannabinoid 2-arachidonoyl glycerol (2-AG). ABHD6 participates in neurotransmission, inflammation, brain energy metabolism, tumorigenesis and other biological processes and is a potential therapeutic target for various neurological diseases, such as traumatic brain injury (TBI), multiple sclerosis (MS), epilepsy, mental illness, and pain. This review summarizes the molecular mechanisms of action and biological functions of ABHD6, particularly its mechanism of action in the pathogenesis of neurological diseases, and provides a theoretical basis for new pharmacological interventions via targeting of ABHD6.